Construction of 3D Hierarchical GO/MoS2/g‐C3N4 Ternary Nanocomposites with Enhanced Visible‐Light Photocatalytic Degradation Performance. Issue 24 (24th June 2019) - Yan, Jia; Song, Zhilong; Wang, Xin; Xu, Yuanguo; Pu, Wenjie; Ji, Haiyan; Xu, Hui; Yuan, Shouqi; Li, Huaming
Abstract: Hierarchical graphene oxide/molybdenum sulphide/carbon nitride (GO/MoS2 /g‐C3 N4 ) ternary nanostructure with visible‐light‐driven photocatalytic property are prepared employing a simple and facile solvothermal method. Systematical characterizations like transmission electron microscopy (TEM), X‐ray diffraction (XRD), Fourier transform infrared spectra (FTIR), UV‐vis diffuse reflectance spectra (DRS), and photoluminescence spectra, have been carried out to figure out composition, structure and optical properties of the ternary composites, accompanied with their physical and chemical interface state among GO, MoS2 and g‐C3 N4 . The GO/MoS2 /g‐C3 N4 ternary photocatalyst exhibits excellent visible‐light‐induced photocatalytic activity for Rhodamine B (RhB) degradation reaching up to 96.7%. More significantly, the hierarchical nanostructured ternary system shows good photostability and reusability with a minor degradation of 1.5%. The enhanced visible‐light photodegradation properties would be owing to the synergetic effects of GO, MoS2 and g‐C3 N4 in the hierarchical ternary GO/MoS2 /g‐C3 N4 nanocomposites favourable for the photogenerated electrons‐holes separation and transfer. In addition, the surface reaction species is also confirmed by the trapping experiments and a reaction mechanism is proposed. Abstract : An effective and simple approach was demonsrated to fabricate heterojunction with nanosized contacts in the graphene oxide/molybdenum sulphide/carbon nitride (GO/MoS2 /g‐C3 N4 ) system for efficient Rhodamine B degradation under visible light irradiation, which attributes to the synergetic effects of GO, MoS2 and g‐C3 N4 in the ternary nanocomposites that is favourable for the photogenerated electrons‐holes separation and transfer.